Kesesuaian Prosedur Pemeriksaan Administratif Dalam Sengketa Kepegawaian: Analisis Putusan PTUN Bengkulu Dalam Perkara Mustarani Vs Bupati Lebong - Dinda Okly Putrinabila Dalimunthe; Kaia Azahra Putri Aimar; Nalani Harumi; Sabrina Aulia Paramitha Yunian (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research employs a normative juridical method by examining statutory regulations, legal principles, and the Bengkulu Administrative Court Decision Number 12/G/2024/PTUN.BKL concerning the civil-service dispute between Mustarani and the Regent of Lebong. The study focuses on assessing the conformity of administrative examination procedures in issuing administrative decisions with positive law and the principles of good governance (AUPB). Using a statute approach and case approach, this research analyzes the use of authority, procedural completeness, and the application of the Standards, Procedures, and Criteria (NSPK) for civil-service management. The findings indicate that the dismissal and reassignment decisions issued by the Regent did not meet essential administrative examination stages such as clarification, factual verification, and mandatory personnel coaching. These deficiencies violated the principles of accuracy, legal certainty, and accountability. The Administrative Court’s annulment of the decisions confirms that the authority of administrative officials is not absolute; it must be exercised procedurally, professionally, and responsibly to protect civil-servant rights and ensure governmental accountability.